WEB-BASED ASSIGNMENT SUBMISSION AND MARKING SYSTEM - Cheah, Sook Hoo (Universiti Malaysia Sarawak, (UNIMAS), 2005)
The Web-Based Assignment Submission and Marking System is a web-based application that aims to provide assignment management services for assignment submission and assignment marking. It is developed to enable the students to submit and the lecturers to mark assignments online anywhere at anytime as long as their computers are connected to the Internet. In addition, students may view the results of their assignment and download marked assignment through the system. This system is implemented using PHP, JavaScript, Cascading Style Sheet (CSS), and Hyper Text Markup Language (HTML). The database for this system runs on MySQL and SQLyog is connected to MySQL host to manipulate the data within MySQL. Apache 1.3.23 is used as the web server and Microsoft Internet Explorer 6.0 is used as the client browser for this system.